INFLUENCE OF VOTING IN ELECTIONS ON RESPONSIVE GOVERNANCE IN NAIROBI CITY COUNTY GOVERNMENT, KENYA - Maina, Ndei; Iravo, Mike; Ombui , Kepha (Journal of Public Policy and Administration, 2021)
Purpose- This study focused on establishing the influence of voting in elections on responsive governance in Kenya. Its main objective was to establish the influence of voting in elections on responsive governance in Kenya. Methodology- Descriptive research design and positivism research philosophy were adopted. The study focused on a target population of 680 respondents from Eighty-five wards within Nairobi County, and data was collected from the following groups of respondents; Civil society representative, religious representative, ward administration representative, youth representative, women representative, the special interest group representative, a representative of the citizens' anticipating county services and a representative of the old aged residents were targeted. A sample size of 139 respondents was determined though purposive sampling technique. Primary data was collected through questionnaires and secondary data through published materials. Data was analysed through SPSS and presented in tables. Hypothesis testing was done through the use of t-test. F test (ANOVA) was also conducted to ascertain the difference between groups on study variable. Findings- The study found that voting in elections has a positive and significant relationship with responsive governance. The study concluded that that citizen's education influences their ability and decision to vote in leaders who are effective in service delivery. The study also concluded that incumbent leader performance influences achievement of county goals. Based on the study findings, the researcher recommends that there is need to establish, County, Sub-County and Ward Citizens Forums to enhance voter awareness of residents in local governance. The forums will specifically enable citizens to engage directly in the planning, policy making and monitoring of service delivery accorded to them. Originality/value - This paper fulfils an identified need in understanding how voting in elections can influence responsive governance. The study therefore recommends that all citizens should be empowered and given the rights to vote in their desired leader. Additionally, free and fair elections should be conducted to ensure that candidates with clear manifestos are elected.